Impact of COVID-19 lockdowns and refugee influx on scabies presentations to dermatology outpatient clinics in Turkey - Rabia Öztaş Kara; Berna Solak; Ahmet Kara (Journal of Infection in Developing Countries)
Introduction: The frequency of scabies and its relationship with the coronavirus disease 2019 (COVID-19) pandemic is a current scientific curiosity in Turkey and worldwide. The data presented in this article will help raise awareness of dermatologists in situations such as pandemic-induced quarantines where scabies can spread rapidly.